إدارة العمليات الريادية - زلوم, هبة نبيل (جامعة بوليتكنك فلسطين - نظم معلومات)
تهدف الدراسة الى ادارة المشاريع الريادية والناشئة من حيث ادارة مخزونها وادارة المحاسبة لديها وادارة الموارد البشرية التي تعمل في المشروع بتطبيق ونظام الالكتروني واحد بدل الاستخدام لنظام الورقي وضياع المعلومات التي تحتويها ، والتطبيق يخدم اصحاب المشاريع الناشئة والريادية ، بحيث يعمل على رفع قدرات وكفاءة الرياديين في ادارة المشاريع لديهم بشكل افضل وكفؤ اكثر ، يتم اتباع منهجية دورة حياة تطوير النظام (WaterFall) وتتكون هذه المنهجية من عدة مراحل اساسية حيث تبدأ بمرحلة التخطيط ثم تحليل النظام ثم التصميم ثم تجهيز النظام ,واخيرا تقديم التوصيات الضرورية للأطراف المعنية بموضوع الدراسة . This study aims to manage the leading and emerging process in terms of inventory management and accounting management. In addition to management of human resources departments that utilizes this electronic application only instead of using the paper-based system. Information included in this this system can be exposed to loss. This application serves start-up project owners and entrepreneurs. This application is designed to raise the capabilities and efficiency of entrepreneurs in the management of projects. (WaterFall) methodology of life-cycle system is adopted in designing (G-sparkle) application. This methodology consists of several basic stages that starts by the planning stage, analyzing, designing and finally processing the system. Initially, the researcher provides recommendations to the parties concerned by.
no of pages 115 , نظم معلومات 2019
Keywords: ادارة الريادة